A chaos-based image encryption algorithm with simple logical functions. (August 2016) - Yavuz, Erdem; Yazıcı, Rifat; Kasapbaşı, Mustafa Cem; Yamaç, Ezgi
Highlights: Proposed an effective chaotic encryption scheme based on confusion and diffusion principles. Introduced bitwise circular rotation operation to increase plaintext sensitivity. Proposed an effective encryption scheme with two independent chaotic functions to increase computing ability. Test results indicate that the proposed encryption method is more secure and fast. Graphical abstract: Abstract: This paper proposes an effective chaos-based encryption algorithm specialised for images. A system of two independent chaotic functions with high sensitivity to initial states, is utilised to sufficiently apply confusion and diffusion principles for images with any entropy. One of the functions is used for shuffling pixel positions while the other for changing the values of pixels. In the resulting new pixel organisation, adjacent pixels with naturally close values will take on considerably different values, making it difficult to crack the encrypted image. To increase resistance of the system to differential attacks, some logical operations such as exclusive-or and circular rotation are used to spread the effect of a slight change in single pixel intensity of plain image over many pixels in cipher-image. A variety of analyses and tests has been carried out to prove the security and the validity of the algorithm. Even with low entropy images the proposed algorithm has been proved to be more secure and faster than the previous algorithms.